2022
DOI: 10.1108/bfj-09-2022-0793
|View full text |Cite
|
Sign up to set email alerts
|

Food inflation and geopolitical risks: analyzing European regions amid the Russia-Ukraine war

Abstract: PurposeThe study's objective is to measure the response of the food prices to the aggregate and disaggregate geopolitical risk events, Russia's geopolitical risks and global energy prices in the context of two European regions, i.e. Eastern and Western Europe covering the monthly data from January 2001 to March 2022.Design/methodology/approachThe authors apply a novel and sophisticated econometric method, the cross-quantilogram (CQ) approach, to analyse the authors’ monthly data properties. This method detects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 67 publications
(137 reference statements)
2
17
0
Order By: Relevance
“…The increase in ECPI has led to an increase in FCPI in the EU. Our findings are consistent with the findings of Sohag et al (2023), who found that rising global energy prices have increased EU food inflation. The transformation of raw commodities and the transportation of food to the final consumer both require energy.…”
Section: Discussionsupporting
confidence: 93%
“…The increase in ECPI has led to an increase in FCPI in the EU. Our findings are consistent with the findings of Sohag et al (2023), who found that rising global energy prices have increased EU food inflation. The transformation of raw commodities and the transportation of food to the final consumer both require energy.…”
Section: Discussionsupporting
confidence: 93%
“…The research papers of the authors [3,8,13,18] were continued in terms of finding relationships between certain indicators of the state of food security and factors influencing its level. A hypothesis is put forward regarding the existence of a direct relationship between the degree of compliance of agricultural production with sustainable development principles and the general level of economic accessibility of food in a specific country.…”
Section: Discussionmentioning
confidence: 99%
“…The author [2] draws attention to the fact that at a time when global stocks are running short, Russia's military aggression in Ukraine is a shock to the whole world. In the paper [3], it was concluded that the measures of geopolitical risk reduce food prices. In addition, the authors emphasize the existence of a tendency to increase food prices.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations